Status Kesuburan Tanah Pada Dua Tutupan Lahan Di Kesatuan Pengelolaan Hutan Lindung (KPHL) Batutegi Lampung - Melya Riniarti; Agus Setiawan (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
Land cover changing would influence the availability of nutriens and others soil properties. In the forest areas, forest clearing would lead land degradation. KPHL Batutegi was catchment area for Batutegi dam. The ilegal logging that still occure in that area raising important question about the soil fertility status in that region. Its related to soil capability to the plant growth. The aims of this study was to get information about soil fertility status in two type of land cover, which was secondary forest and one year mixed coffee plantation. Soil sample was taking by purpose sampling on two type of land cover in KPHL Batutegi. One year mixed coffee plantation opened by illegal loging with fired. Intact soil samples were taken using the ring samples, while for the disturbed soil was done by the composite. Parameters observed were nutrients contain (N, P, and C-organic), pH, CEC, soil thickness, total pores and textur. The result showed that there no different on nutrient status and chemical soil properties between two land cover type. It was important from this study obtained that about 10 cm soil lost after one year land clearing from secondary forest to mixed coffee plantation. Keywords: forest, land cover, nutrient, soil fertility